Diabetic Foot - Singh, Satyam; Dolas, Paridhi; Shaheed, Raza; Shukla, Samarth (A Concise Clinicopathological Handbook of Diabetes Mellitus, 2021)
Diabetic foot is considered as most avoidable complication amongst all diabetic complications which can be in form of blisters/ ulcers/ wound infections/ gangrene. It can be prevented by proper preventive medicine. Surgical treatment involve wound offloading, wound debridement, reconstructive surgery.